Morphological and Agronomic Response of Grafted Bitter Gourd (Momordica Charantia) to Different Cucurbitaceae Root Stocks - Pattung, Boyet (International Journal of Sustainability and Advanced Integrated Research, 2026)
The study was conducted to evaluate the morphological, agronomic and economic performance of grafted bitter gourd. Specifically to determine the effects of different rootstocks on growth, physiological responses, yield and returns of bitter gourd. The experiment was laid out using Randomized Complete Block Design (RCBD) with three treatments replicated three times. The Treatments were: T₁ – non-grafted bitter gourd, T₂ – bitter gourd grafted onto ridge gourd (Luffa acutangula), and T₃ – bitter gourd grafted onto squash (Cucurbita maxima). Results showed that Grafting on ridge gourd rootstock gave higher number of secondary and tertiary branches, the biggest stem diameter and longest root. Significant effects were also observed in some reproductive and yield characters. Grafted plants on ridge gourd rootstock resulted to the highest number of female flowers, marketable fruits, total fruits per plot, fruits per plant, weight of fruit, length of fruit, yield per plant, yield per plot and yield per hectare. The highest yield of 15.61 t ha-1 was obtained from plants grafted on ridge gourd rootstock. The fruit diameter; vine length; and number of non-marketable fruits were not affected by the treatments. Cost and return analysis revealed that the grafted ampalaya using ridge gourd rootstock secured the highest net income and ROI of 186.97% which indicates higher profitability than the rest of the treatments. From the study conducted, it was found out that the most suitable rootstock for grafted ampalaya for better growth, yield, stress tolerance, and profitability under field condition is the ridge gourd (Luffa acutangula).